PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY BERBANTUAN ASSEMBLR EDU PADA MATERI PANCASILA DALAM KEHIDUPANKU KELAS V SEKOLAH DASAR - Meiranda Sartika; Diana Pramesti; Rifki Hanif Setiawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Based on preliminary observations conducted at SD Negeri 28 Pangkalpinang, teachers were found to experience constraints in developing technology-based instructional media. The demand for learning media was strong in a student-led needs analysis (88.75 percent), suggesting that these tools are indispensable in the classroom. Therefore, the purpose of this study was to create and test augmented reality (AR) learning materials using Assemblr Edu on the subject of "Pancasila in My Life" with primary school children in fifth grade. The research strategy used in this study was an R&D approach. The ADDIE paradigm, which includes the five steps of analysis, design, development, implementation, and evaluation, served as a framework for the development of the augmented reality learning media utilizing Assemblr Edu. The main research instruments used to gather data were tests, questionnaires, and interviews. For the purpose of determining whether or not the created media were practical, descriptive quantitative methods were applied to the collected data. Validity, practicability, and efficacy were all factors that the created learning materials achieved. Out of the total responses, 93.3% were deemed "very valid," 80.0% were deemed "valid" by material experts, and 82.2% were deemed "valid" by media experts. The learning media were shown to be 100% practical in both small-scale and large-scale testing. Additionally, 90% of teachers were satisfied with the results of the survey. An efficiency rate of 89% was produced by the N-Gain computation, classifying it as highly effective. The Pancasila in my life topic for fifth-grade elementary school pupils, as taught by Assemblr Edu through Augmented Reality learning media, is thus valid, practical, and effective.